INSULIN STIMULATES AUXIN-DEPENDENT CELL PROLIFERATION IN NT-1 TOBACCO SUSPENSION CELL CULTURES - Fierros-Romero, G.; Mellado-Rojas, M. E.; Beltrán-Peña, E. M. (Nexo Revista Científica, 2016)
Insulin regulates growth in plants such as maize and beans, through cell proliferation. In this study we observed that in NT-1 tobacco cell cultures, the hormone regulates cell proliferation dependent on the presence of auxins. The cultures where the auxin concentration was limited showed a low mitotic activity, which was reestablished by the addition of 1.23 nM of insulin through the expression of the cyclin B, CDKB, E2F, G protein subunit β ARC A and glutation -S-transferase (GST) genes. The cultures also presented an increase in dry weight and small cells corresponding to a phenotype with high cell division. On the other hand, it has been reported that the absence of auxins in this type of culture of suspended tobacco cells leads to a partial synchronization, and in this system insulin also promoted proliferation, increasing the expression of the E2F gene.